2023
DOI: 10.1021/acsami.3c04549
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Confined Fe7S8 Nanoparticles Anchored on a Porous Nitrogen-Doped Carbon Nanosheet Skeleton for High-Rate and Durable Sodium Storage

Abstract: Iron sulfides are widely explored as anodes of sodium-ion batteries (SIBs) owing to high theoretical capacities and low cost, but their practical application is still impeded by poor rate capability and fast capacity decay. Herein, for the first time, we construct highly dispersed Fe7S8 nanoparticles anchored on a porous N-doped carbon nanosheet (CN) skeleton (denoted as Fe7S8/NC) with high conductivity and numerous active sites via facile ion adsorption and thermal evaporation combined procedures coupled with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 77 publications
0
15
0
Order By: Relevance
“…Between 300 and 500 °C, the weight decreases sharply due to the combustion of carbon nanofibers to produce CO 2 . Then, from 500 to 700 °C, H-CoS 2 /FeS 2 in these composites is oxidized to from H-Co 3 O 4 /Fe 2 O 3 . According to the TG results, the carbon content of H-CoS 2 /FeS 2 @CNFs-2 is estimated to be 48.9 wt %.…”
Section: Resultsmentioning
confidence: 99%
“…Between 300 and 500 °C, the weight decreases sharply due to the combustion of carbon nanofibers to produce CO 2 . Then, from 500 to 700 °C, H-CoS 2 /FeS 2 in these composites is oxidized to from H-Co 3 O 4 /Fe 2 O 3 . According to the TG results, the carbon content of H-CoS 2 /FeS 2 @CNFs-2 is estimated to be 48.9 wt %.…”
Section: Resultsmentioning
confidence: 99%
“…75-0039), [25] except for the diffraction peak at 26.1°arising from the carbon nanosheets. [26] Regarding the sample of the CoS 2 /FeS 2 /C hybrid composite, the characteristic peaks at 32.4°, 36.5°, 40.1°, 46.7°a nd 55.3°can be readily indexed to the cubic phased CoS 2 (JCPDS No. 41-1471), [27] while the other peaks appearing at 33.1°, 37.1°, 40.8°, 47.4°and 56.3°are also detected attributing to the cubic phased FeS 2 (JCPDS No.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that the high content of pyridinic N and pyrrolic N can provide more defects in the carbon materials acting as electrochemical active sites, and boost the adsorption of Na + during the repeated cycling process. [20,26,42,43] The N 2 adsorption-desorption isotherms and pore size distribution curves of the CoS 2 /FeS 2 /C and CoS 2 /FeS 2 hybrid composites are displayed in Figure S2. It is found that both samples present typical type IV isotherms with mesoporous features.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations